2013
DOI: 10.1038/srep02066
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for semen collection and artificial insemination in large parrots (Psittaciformes)

Abstract: The paper described a novel technique for semen collection in large psittacines (patent pending), a procedure which was not routinely possible before. For the first time, a large set of semen samples is now available for analysis as well as for artificial insemination. Semen samples of more than 100 psittacine taxa were collected and analysed; data demonstrate large differences in the spermatological parameters between families, indicating an ecological relationship with breeding behaviour (polygamous versus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 21 publications
0
25
0
9
Order By: Relevance
“…In psittacines, semen collection via massage method and semen analysis have been performed in smaller species [Samour et al, ; Anderson et al, ; Samour, ; Stelzer et al, , ; Neumann et al, ], but rarely reported in larger parrots [Brock, ; DellaVolpe et al, ], and with only moderate success rates. The application of a recently developed apparatus for electro‐stimulated semen collection enabled the collection of semen samples from 109 psittacine species, including the Spix's macaw [Lierz et al, ]. Beside spermatozoa, round cells have been described within the ejaculate of birds, which were regarded as spermiophages [Stelzer, ] or “round bodies” [Bailey, ] with unknown function and origin.…”
Section: Introductionmentioning
confidence: 99%
“…In psittacines, semen collection via massage method and semen analysis have been performed in smaller species [Samour et al, ; Anderson et al, ; Samour, ; Stelzer et al, , ; Neumann et al, ], but rarely reported in larger parrots [Brock, ; DellaVolpe et al, ], and with only moderate success rates. The application of a recently developed apparatus for electro‐stimulated semen collection enabled the collection of semen samples from 109 psittacine species, including the Spix's macaw [Lierz et al, ]. Beside spermatozoa, round cells have been described within the ejaculate of birds, which were regarded as spermiophages [Stelzer, ] or “round bodies” [Bailey, ] with unknown function and origin.…”
Section: Introductionmentioning
confidence: 99%
“…Sendo assim, para suindaras, nesta análise, seria possível sugerir que as maiores médias de medidas de área de cloaca podem ter relação com a produção de amostras com sêmen. (LIERZ et al, 2013;FISCHER et al, 2014). Em nosso estudo, vimos que, para a maioria das espécies, houve uma porcentagem baixa de manifestações de vocalização e agitação, o que nos leva a considerar este protocolo de eletroestimulação passível de ser realizado sem a utilização de sedativos ou anestésicos.…”
Section: Resultsunclassified
“…Em virtude do alto grau de contaminação do sêmen por fezes e urina, baixa concentração espermática e dificuldades na padronização, essa metodologia foi ignorada por quase 30 anos, quando Lierz et al (2013) avaliaram o emprego da eletroestimulação em 151 espécies de psitacídeos (SAMOUR et al, 1985;LIERZ et al, 2013;FISCHER et al, 2014). Este estudo e o publicado por Fischer et al (2014) (LIERZ et al, 2013).…”
Section: Lista De Figurasunclassified
See 2 more Smart Citations